2005
DOI: 10.1614/wt-04-245r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Winter Cereals for Weed Control in Conservation-Tillage Nontransgenic Cotton

Abstract: The increased use of conservation tillage in cotton production requires that information be developed on the role of cover crops in weed control. Field experiments were conducted from fall 1994 through fall 1997 in Alabama to evaluate three winter cereal cover crops in a high-residue, conservation-tillage, nontransgenic cotton production system. Black oat, rye, and wheat were evaluated for their weed-suppressive characteristics compared to a winter fallow system. Three herbicide systems were used: no herbicide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 10 publications
6
71
1
1
Order By: Relevance
“…Spatial scale is particularly important in pest management because landscape features affect species interactions, microclimates and weather patterns and can have notable effects on pests by changing habitat patterns and immigration rates (Colunga-G et al 1998). Initially attempts were made to apply the theory of island biogeography (MacArthur & Wilson 1963, 1967 to agricultural settings (Reeves et al 2005). By treating crop fields as islands, the theory predicts that the number of species inhabiting a field is the result of immigration and extinction rates, leading over time to equilibrium in species richness.…”
Section: Issues Of Scalementioning
confidence: 99%
“…Spatial scale is particularly important in pest management because landscape features affect species interactions, microclimates and weather patterns and can have notable effects on pests by changing habitat patterns and immigration rates (Colunga-G et al 1998). Initially attempts were made to apply the theory of island biogeography (MacArthur & Wilson 1963, 1967 to agricultural settings (Reeves et al 2005). By treating crop fields as islands, the theory predicts that the number of species inhabiting a field is the result of immigration and extinction rates, leading over time to equilibrium in species richness.…”
Section: Issues Of Scalementioning
confidence: 99%
“…Cereal rye (Secale cereale L.) has been well documented for both high biomass potential and allelopathic properties by several researchers [42,43,[48][49][50][51][52]. Several studies on cover crops have reported excellent early-season weed control that can preclude the use of preemergence herbicides in crops [39,41,[52][53][54][55][56][57][58][59]. However, the success of a cover crop in early-season weed suppression is determined by the biomass production potential which varies with year, location and management practices [37,48,53,56,60].…”
Section: Introductionmentioning
confidence: 99%
“…to reduce weed germination and growth over winter fallow conservation systems due to mulching and allelopathic affects (Barnes and Putnam 1985;Teasdale 1991;Reeves et al 2005;Price et al 2006;2008a;2008c;Culpepper et al 2009; ]). Previous research has also shown that weed suppression by residue is mainly influenced by biomass amount (Teasdale et al 2000;Price et al 2005).…”
Section: Countmentioning
confidence: 99%